Design of security mechanism for cyber-physical systems - Chen, Shuo (2014)
As the next generation of network, the emerging cyber-physical systems (CPS) are going to connect all of the objects of physical and cyber world. Machine to machine (M2M) communication is a fundamental part of the CPS which utilizes both wireless and wired systems to monitor physical or environmental conditions and exchange the information among different systems without direct human intervention. While being a promising technology which has potentials to become a market-changing force for a wide variety of real-time monitoring applications, M2M communication still faces lots of threats. Even though many solutions have been found to address the security issues of the M2M communication in the literature, there are some security vulnerabilities that yet to be solved. In the thesis, we first introduce the background, architecture security threats and security requirements of M2M communication in CPS. Subsequently, we review the important security solutions for M2M domain proposed in recent literatures from three aspects: detection, authentication and key management, explore the emerging technologies -- IPv6 over Low power Wireless Personal Area Networks (6LoWPAN) and Constrained Application Protocol (CoAP), which would be applied to M2M communication in the future and review the current security solutions for 6LoWPAN in the literature as well. Then we propose three authentication schemes for M2M communication: a dynamic-encryption authentication scheme for M2M security in cyber-physical system, an authentication scheme with identity-based cryptography (IBC) for M2M security in cyber-physical systems and an authentication scheme for multi-domain M2M security in cyber-physical systems. The proposed dynamic-encryption scheme could avoid directly stealing and modifying of the mobile devices’ and the sensors’ ID. The dynamic-key generation mechanism in dynamic-encryption scheme could not only provide a reliable one-time-password among M2M service provider (MSP), mobile devices and sensor nodes but also save the computing resource of the sensor nodes. The application of integrated IBC in the authentication scheme with IBC could achieve the message authentication without key escrow problem and reduce the threat of compromise attack to a great extent. The regular updating of secret key could also make the key guessing attack meaningless. In the third scheme, the communication scenario in which the sensor nodes from different domains communicate with each other without human intervention has also been considered. Our analysis indicates that the mutual authentication and the ability of withstanding multiple attacks could be accomplished by the proposed solutions and the balance between system performance and security has been achieved.